Effectiveness of using an online instructional video for preventing infections among Thai patients with cancer: A quasi-experimental study - Viseskul, Nongkran; Kasatpibal, Nongyao; Suwan, Natthawan; Chaywong, Yuwalee; Pholdee, Narumon (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Patients with cancer are more likely to develop infections from several factors, and an infectious complication is the leading cause of death in this population. Therefore, nurses should provide educational media to these patients for infection prevention. Objective: This study aimed to examine the effectiveness of using an online instructional video to prevent infections among patients with cancer in Thailand. Methods: A quasi-experimental design was conducted from May 2020 to March 2021 at a cancer hospital in northeast Thailand. The participants consisted of 54 patients with cancer (27 each in the experimental and control group). The experimental group participants received four weeks of online video instruction at home, while the control group received the usual education from nurses. The data collection instruments included a demographic data questionnaire, a knowledge test, an infection prevention practice questionnaire, and a video media satisfaction questionnaire. Statistical analyses included descriptive statistics, chi-square test, Fisher’s exact test, paired t-test, and independent t-test. Results: After receiving the online instruction video, the experimental group had a significantly higher score for infection prevention knowledge, increasing from 17.52 to 20.93 (t = -6.575, p <0.001), and infection prevention practice, rising from 52.07 to 61.33 (t = -3.954, p = 0.001). The control group had no significant increase in the knowledge score (17.04 to 18.04) (t = -1.328, p = 0.100) or practice score (53.41 to 54.44) (t = -0.797, p = 0.217). The experimental group showed a significantly higher mean knowledge score (t = 4.473, p <0.001, large effect size with a Cohen’s d of 1.22) and practice score (t = 3.121, p = 0.002, large effect size with a Cohen’s d of 0.85) during post-intervention than the control group. Conclusion: The findings support the use of online video as instructional media to enhance knowledge and practices regarding infection prevention among patients with cancer. This online video should be implemented for nurses and healthcare providers to promote knowledge and practices in the prevention of infections among patients with cancer in other hospitals. Trial Registry Number: Thai Clinical Trials Registry (TCTR20241030009)